Earthquake And Volcanic Eruption Disaster Education For Aisyiyah Athfal Batoh Kindergarten Students - Soviana, Widya; Sunarty, Risma; Sugiarti, Annisa; Yanti, Veri; Mubarak, Dzakiyul; Akmal, Muhammad Nur (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
This Community Service Program (PKM) aims to provide early disaster education to kindergarten children in disaster-prone areas. Utilizing an interactive approach through play and singing, this program imparts foundational knowledge about earthquakes and volcanic eruptions, along with essential self-rescue steps. The program also benefits teachers by enhancing their skills in delivering disaster education to young children, and it supports schools in incorporating educational disaster-related games into annual activities. The results indicate that this enjoyable and participative learning approach effectively improves children’s understanding and preparedness for potential disasters. Additionally, the program fosters a disaster-aware culture within the school environment, with the hope that it can be replicated in other schools located in high-risk areas.